Heat balance analysis for an electric car - Rusowicz, Artur; Kowalski, Bartosz (International Conference “Environmental Engineering”, 2026)
The paper focuses on the analysis and simulation of thermal management systems in electric vehicles. In the computational section, heat exchange in the passenger cabin and the electric drive system was modeled using advanced engineering software Siemens Amesim. These models were employed to simulate the cabin’s heat balance and to calculate heat losses in the drive system in order to determine the thermal load on the cooling and air conditioning systems. Based on the results, the impact of operating conditions on heat exchange with the environment was analyzed, and directions for further development of cooling systems in electric vehicles were proposed. A well-described Tesla Model SR 2021 RWD electric vehicle was analyzed. Calculations were performed for three variants, one with a stationary vehicle, the second with a variable ambient temperature, and the third with a variable vehicle speed. The calculations revealed a significant impact of ambient temperature on heat flows penetrating the car’s structure, and in the case of increasing car speed, a significant demand for battery and engine cooling.
Keywords: electric vehicle; heat fluxes; heat balance; thermal management system